(untitled) (Research, Society and Development, 2022)
Studies using starch to produce biodegradable materials have proved attractive due to its availability and low cost in relation to commercial biodegradable polymers, such as poly (lactic acid) and others. Starch-based materials do not have adequate mechanical properties for production and use on a commercial scale, requiring mixtures (blends) with other biodegradable polymers to improve these properties. However, these blends need compatibilizers due to the immiscibility between the starch and the polymer. The present work aimed to study the effect of different compatibilizers (3-(trimethoxysilyl) propyl methacrylate, citric acid, and maleic anhydride) on the functional properties of biodegradable starch and poly (lactic acid) (PLA) materials produced by extrusion and thermoplastic injection. Citric acid was considered the best compatibilizer for these materials because it improved the processability, and the materials presented properties suitable for applications where good mechanical resistance is required. In addition, the materials containing citric acid and maleic anhydride were more uniform from the morphological point of view.